Deteksi Kadar Asap Rokok di Dalam Ruangan Menerapkan Metode Fuzzy Logic Mamdani - Fauzan Helmi (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
The number of sufferers of respiratory disorders, both young and adult caused by cigarette smoke, has increased every year, from 192 countries it is stated that around 40% of children in the world are exposed to cigarette smoke and more than 30% of adults become passive smokers. Cigarette smoke using an Arduino equipped with a gas sensor makes it easy for early detection when someone wants to smoke in the room, the room should be clean of cigarette smoke and equipped with a temperature sensor if too much smoke can make the temperature in the room it changes. The design of the smoke level detector in cigarettes with smoke sensors and temperature sensors uses the mandani fuzzy logic algorithm, equipped with red and white led indicators, a buzzer to provide information in the form of sound, an LCD display that functions to display smoke and temperature information that can be obtained in the room. , as well as a fan as an output to remove cigarette smoke and cool the room temperature